Progress in research on seniors' well-being in tourism: A systematic review. (October 2022) - Chang, Lu; Moyle, Brent D.; Dupre, Karine; Filep, Sebastian; Vada, Sera
Abstract: Research on well-being has experienced exponential growth in tourism studies. However, knowledge about well-being of seniors in tourism is still limited, and thus conceptually underdeveloped, despite the growth of the ageing population and increased research focus on the subject. Consequently, the purpose of this review is to provide a holistic understanding of seniors' well-being in tourism, delineate the current research status, then identify gaps and future avenues for research. A systematic quantitative literature review was conducted, leading to 56 eligible articles extracted for subsequent analysis. By mapping the current state of knowledge, the study indicates a need for a comprehensive theoretical framework based on a holistic view of seniors' well-being in tourism. The findings of the systematic review suggest the need for a eudaimonic approach to the topic and research from residents' perspectives. Suggestions are made to investigate constraints to well-being and cultural differences in conceptions of seniors' well-being in tourism. Graphical abstract: Unlabelled Image Highlights: Explores the evolution of knowledge on seniors' well-being in tourism. Reveals studies are predominantly atheoretical. Unearths a lack of eudaimonic-focused studies. Uncovers a gender bias and a dominance of quantitative approaches. Presents a conceptual model articulating six key areas for future research.